2009
DOI: 10.1021/tx8003246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mainstream Cigarette Smoke on the Global Metabolome of Human Lung Epithelial Cells

Abstract: Metabolomics is a technology for identifying and quantifying numerous biochemicals across metabolic pathways. Using this approach, we explored changes in biochemical profiles of human alveolar epithelial carcinoma (A549) cells following in vitro exposure to mainstream whole smoke (WS) aerosol as well as to wet total particulate matter (WTPM) or gas/vapor phase (GVP), the two constituent phases of WS from 2R4F Kentucky reference cigarettes. A549 cells were exposed to WTPM or GVP (expressed as WTPM mass equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 37 publications
5
71
1
1
Order By: Relevance
“…These data correlate with human microarray data that demonstrated an antioxidant response to cigarette smoke through the induction of genes associated with glutathione metabolism (Spira et al, 2004). Further, Vulimiri and colleagues (Vulimiri et al, 2009) observed increased levels (16.4-fold) of o-phosphoethanolamine, a marker of phospholipid degradation that may indicate cell membrane damage. Additional observations included increased arachidonic acid levels that may suggest an inflammatory response and markers (e.g.…”
Section: Pulmonary Toxicity (Cigarette Smoke)supporting
confidence: 75%
See 2 more Smart Citations
“…These data correlate with human microarray data that demonstrated an antioxidant response to cigarette smoke through the induction of genes associated with glutathione metabolism (Spira et al, 2004). Further, Vulimiri and colleagues (Vulimiri et al, 2009) observed increased levels (16.4-fold) of o-phosphoethanolamine, a marker of phospholipid degradation that may indicate cell membrane damage. Additional observations included increased arachidonic acid levels that may suggest an inflammatory response and markers (e.g.…”
Section: Pulmonary Toxicity (Cigarette Smoke)supporting
confidence: 75%
“…There is a paucity of relevant metabolomic information for application to human health risk assessment of environmental chemicals. To date, the available literature suggests an informative role of metabolomics in understanding the mode of action of environmental xenobiotics (Vulimiri et al, 2011;Vulimiri et al, 2009). …”
Section: Metabolomics Approach In Investigating Environmental Chemicamentioning
confidence: 99%
See 1 more Smart Citation
“…Differences were observed between the effects of whole smoke and the gas/vapor phase from a single cigarette type on the metabolic pathways of human lung epithelial cells (Vulimiri et al, 2009), suggesting that cigarette smoke fractions can affect these pathways differentially. Exposure of NCI-H292 cells, a human lung epithelial cell line, to whole smoke demonstrated increases in expression of Muc5AC, an important form of mucin, and release of interleukin (IL)-6, IL-8, and MMP1 (Phillips et al, 2005).…”
mentioning
confidence: 99%
“…Background art discloses that smoking triggers enzymatic beta-oxidation in mitochondrial compartments and degradation of the cellular defense system is shown with alveolar epithelial carcinoma cells [90]. Individual history of depression and/or dosage of psychopharmaca had to be carefully considered to guide persons at risk during long cessation periods [91].…”
Section: Discussionmentioning
confidence: 99%